EXAMINING THE DETERMINANTS OF RENEWABLE ENERGY PRODUCTION IN ASEAN COUNTRIES - Huy, Khanh Nguyen (International Journal of Application on Economics and Business, 2024)
This study investigates the determinants of renewable energy production in ASEAN countries, focusing on the factors influencing the transition to sustainable energy sources in the region. By utilizing the panel data from 2000 to 2020 with Pooled OLS, Random Effect model and Fixed Effect model, the research explores the explainatories of renewable energy production in ASEAN. The findings reveal that renewable energy consumption, economic growth and FDI have a positive and significant relationship with renewable energy production, while trade openness and urbanization have significant association with REP. It suggests the importance of suitable policy design to support renewable energy production in ASEAN, emphasizing the role of government-backed energy policies. Overall, this research contributes valuable insights for policymakers and stakeholders in the renewable energy sector, offering guidance for promoting sustainable energy practices and addressing climate change challenges in ASEAN countries.